The Role of Pensioners in the American Electorate - L. F. Lebedeva; E. V. Emelianov (Управление)
The article examines fundamental demographic changes in the USA that have been shifting the electorate and as a result - American politics; with wide gaps between the generations on key social, economic, political issues. The US presidential elections since 1980 were dominated by baby boomers (born 1946-1964) and prior generations, who have cast the vast majority of votes in every presidential election. The 2016 electorate has been the most diverse in the US history due to strong growth of young generations, and especially among Hispanic eligible voters. Millennials (born 1981–1998) and X generation (born 1965-1980) surpassed Baby Boomers and more old generations whose choices differ significantly in many fields; but the key problem is who really votes. The age structure of the American electorate and its influence on the election results; the role of pensioners and those, who’ll retire in the nearest future, as voters at the federal and state levels are in focus.